"Welcome on board": Overall liking and just‐about‐right ratings of airplane meals in three different consumption contexts—laboratory, re‐created airplane, and actual airplane. Issue 2 (3rd March 2017) - Holthuysen, Nancy T. E.; Vrijhof, Milou N.; de Wijk, René A.; Kremer, Stefanie
Abstract: The main objective of this study was to evaluate the effect of contexts on overall liking and just‐about‐right (JAR) ratings of airplane meals. A rice dish (meal type A) and a pasta dish (meal type B) were assessed. Per meal type, two variants were produced (variant 1 and 2). Two hundred forty‐two consumers were randomly allocated to evaluate one of the four meals, first in a laboratory setting and then in a re‐created airplane environment. In addition, 222 passengers did the same assessments during an actual flight. Specific meals (A1, B1) were less liked in the laboratory than in the re‐created airplane. In general, no differentiation in overall liking occurred per meal type between the two tested variants in the laboratory, whereas these two variants were significantly differentiated in liking in the re‐created airplane and the actual airplane. Mean overall liking ratings in the re‐created airplane did not significantly differ from the mean overall liking ratings in the actual airplane. The observed JAR ratings did not differ much between the re‐created airplane and the actual airplane. In summary, the re‐created airplane as a testing location produced more similar test results to the actual airplane than the traditional laboratory. Practical applications: Sensory consumer testing in re‐created contexts may produce results with a higher external validity than laboratory testing and therefore offer a cost‐efficient alternative to extensive sensory consumer testing in real‐life contexts.